Intercultural Sociohealth Mediation: Health communication strategy in Hospital Universitario Poniente - Segura Garcia, Maria Teresa; Alaoui Benabderrahman, Nivine; Salas Antolinez, Agustín (Revista Española de Comunicación en Salud, 2023)
The Comarca del Poniente is a region that receives a migrant population with linguistic and socio-cultural diversity. This diversity, in the healthcare field, constitutes a communication barrier with migrant patients, that determines poorer health outcomes and equality access to healthcare. Intercultural Social and health mediation Project (ISHM): In order to guarantee effective communication between the patient and the professional, in Hospital Universitario Poniente in 2020, was created the ISHM Project, whose objective is to implement a care model with an intercultural perspective. During the period 2020 and 2022, the demand for mediation comes mainly from the care area, with the outpatient area being where most actions have been carried out: 2020 (63%), 2021 (61.6%), 2022 (68%); and the most demanded actions are the face-to-face ones 2020 (86%), 2021 (94%), 2022 (95%). With regard to the gender perspective, the female sex was the one with more needs of actions: 2020 (67%), 2021 (67%), although in 2022 the need was balanced (54%). The results confirm the need and relevance of the ISHM in the Andalusian Public Health Service to improve equal accessibility to health care, in those health care centers with similar population characteristics.